Analysis of Legal Unification toward the National Legislation Program in Indonesia - Ahmad Althof 'Athooillah; Muhammad Faisol (Rechtenstudent, 2023)
This study aims to identify and reconstruct various national legal issues. The results of the study were obtained by emphasizing that national law reform is a political process whose success depends on the balance of power between actors within it so that a dialectical process involving all components is carried out by improving legislation. The type of research used is library research which focuses on the library. Data sources are obtained by tracing the literature as well as regulations and norms related to the issues to be studied which originate from books on legal politics, the development of national law, and the science of legislation. The results of this study are (1) That the concept of legal unification in the National Legislation Program is that it must ensure the integration of the nation and state both territorially and ideologically as well as integrating nomocracy (2) because legal unification has succeeded in producing a legal building with modern characteristics with the characteristic of accelerating the integration process, namely development, unity & unity (3) That the conception of legal unification in the future amidst legal pluralism is through the mechanism of harmonization and synchronization of laws and regulations by taking into account several aspects namely legal substance, legal structure, legal culture, and supporting infrastructure.